The AMIGAS Model: Reconciling Prejudice Reduction and Collective Action Approaches Through a Multicultural Commitment in Intergroup Relations. Issue 1 (March 2022) - Urbiola, Ana; McGarty, Craig; Costa-Lopes, Rui
Social psychology's search for ways to address intergroup inequality has grappled with two approaches that have been considered incompatible: (a) the prejudice reduction approach, that argues that changing individual negative attitudes will undermine the basis for discrimination and lead to intergroup harmony; and (b) the collective action approach, that argues that social protest and activism can improve the position of disadvantaged groups. The problem is that efforts toward prejudice reduction may serve to suppress genuine efforts to change. We propose the Achieving Multicultural Integration of Groups Across Society (AMIGAS) model, in which a multicultural commitment is proposed as a driver of both improved intergroup evaluations and promotion of collective action for reduced inequality, especially in contexts where there are conditions for a respectful intercultural dialogue . The AMIGAS model is a theoretical advance in the field of intergroup relations and a basis for implementing effective egalitarian policies and practices.